Climate Change and the Effects of Desert Dust Storms on Children’s Respiratory Health: Public and Stakeholder Awareness, Perceptions, and Practices in Cyprus - Kinni, Paraskevi (My University, 2025)
This doctoral thesis investigates the perceptions, experiences, responses, and adaptive behaviours of different stakeholder and community groups to the health impacts of Desert Dust Storms (DDS) in Cyprus, with particular emphasis on children’s respiratory healthThe overall aim was to examine how institutional actors, health professionals, teachers, parents, and the public perceive and respond to DDS-related risks, in order to inform public health preparedness and resilience strategies.parents and the general public. Guided by the Health Belief Model (HBM), the research employs an exploratory sequential mixed-methods design, combining qualitative methods (interviews and focus groups) with quantitative surveys, across five interrelated studies conducted at both institutional and community levels.comprising five interrelated studies to explore both individual-level responses and systemic preparedness. At the institutional level, the first study involved stakeholders from Cyprus, Greece, and Israel (n=49), whose responses highlighted limited awareness of the full spectrum of DDS health effects, gaps in policy, and weak dissemination of public guidance. The second study surveyed School Health Visitors (n=78), showing moderate preparedness in supporting children with asthma during DDS events but a lack of systematic protocols. At the community level, the qualitative phase included a focus group with teachers (n=6), who reported infrastructural challenges and unclear school-level guidance, and interviews and focus groups with parents (n=27), which revealed the heightened vulnerability and burden experienced by families of asthmatic children. Finally, a quantitative cross-sectional survey of the general public (n=224) explored perceptions and adaptive behaviours. Exploratory factor analysis identified key benefit and barrier dimensions, while regression models showed that perceived benefits of personal protective measures (mask use, staying indoors) and female gender were the strongest predictors of adaptive behaviour. Findings across studies confirm that DDS are recognised as a significant respiratory health threat, yet preparedness remains fragmented, with insufficient coordination at institutional levels. Parents of children with asthma reported disproportionate emotional, financial, and health-related burdens. Teachers and SHVs identified regulatory and infrastructural gaps, while public survey results underscored the role of health beliefs and social determinants in shaping protective actions. Collectively, these findings highlight the urgent need for coordinated communication, targeted interventions, and systemic policy measures to protect vulnerable populations,particularly children, from the health impacts of DDS in Cyprus. By offering empirical insights, this study supports the development of clear public health messaging and coordinated policy actions to enhance resilience to DDS in Cyprus.
Keywords: Desert Dust Storms; Children’s Respiratory Health; Health Belief Model; Public Perception; Adaptive Behaviour; Cyprus